Learning at work in female-dominated and male-dominated industries: A PIAAC study - Joshua C. Collins; Tobin Lopez; Jill Zarestky; Ellen Scully-Russ (Adult Education Research Conference, 2020)
Learning at work has the potential to be an important contributor to employee performance and professional advancement. Yet, gender inequality is prevalent in many workplaces and may influence the types and quality of learning to which employees are exposed. This study’s purpose was to examine the relationship between female- and male-dominated industries and learning at work as measured by the Program for the International Assessment of Adult Competencies (PIAAC). For those industry sectors determined to be female- or male-dominated, we used a linear regression model to determine whether a relationship exists between gender dominance and learning at work based on the independent variables gender, education level, and race. Results indicate workers in female-dominated industries engage in more learning at work than those in male-dominated industries. We conclude gender-dominance may influence workplace culture and social interactions, thereby affect learning at work.
Keywords: workforce development; gender; PIAAC; quantitative